Educomunicação na abordagem CTSA (ciência, tecnologia, sociedade e ambiente): formação continuada de professores de ciências da natureza em pelotas (RS) - (:unkn) unknown (Universidade Federal do Pampa, 2025)
The COVID-19 pandemic has highlighted the urgency of effective science education, highlighting the importance of the CTSA (Science, Technology, Society, Environment) approach in natural science education. The main objective of this study is to investigate possibilities and challenges, through continuing education and communication, for the inclusion of the CTSA approach in natural science education in the municipal public school system of Pelotas.
Educommunication in the CTSA approach (science, technology, society and environment): continuing education for natural science teachers in Pelotas (RS)
Keywords: Comunicação; Aprendizagem significativa; Transformação; Intervenção pedagógica; Questões socioambientais; Communication; Pedagogical intervention; Meaningful learning; Socio-environmental issues; Transformation; CIENCIAS HUMANAS